Kajian Status Gizi Balita Berdasarkan Pola Asuh dan Dukungan Keluarga - Suharmanto Suharmanto; Lalu Dedy Supriatna; Dyah Wulan Sumekar Rengganis Wardani; Bahjatun Nadrati (Politeknik Kesehatan Tanjung Karang, 2021)
According to World Health Organization, more than 50% of infant and child deaths are related to malnutrition. This study aims to determine the relationship between parenting and family support with the nutritional status of toddlers. This study is an analytical study with a cross-sectional approach. This research was conducted at Bintang Ceria Kindergarten, Jati Agung Subdistrict, South Lampung in October-November 2019. The population in this study were all toddlers and their mothers. The inclusion criteria of this study were toddlers and mothers who were willing to be respondents, while the exclusion criteria were toddlers who came with a caregiver (non-mother). The sampling technique was a total sample of 85 toddlers. The instruments used in this study were a questionnaire on parenting styles and family support as well as measuring nutritional status using a scale and a stadiometer to use bodyweight for height. The data was collected by weighing and measuring the toddler's height, then calculating the z-score, and distributing questionnaires containing questions on parenting and family support for the mothers of the children. Data analysis used univariate analysis in the form of percentage and bivariate analysis using the Spearman test. The study found that there is a relationship between parenting styles and family support with the nutritional status of toddlers. Families need to pay attention to and fulfill the needs of balanced nutritional intake for toddlers by providing more support and attention to their toddlers.